T1 and T2 mapping – basic principles and clinical application - K. Genova; D. Kostova-Lefterova (Българска кардиология, 2022)
Cardiac magnetic resonance tomography is widely used method in the diagnosis of cardiovascular diseases. In the last decade, new techniques have been developed to obtain quantitative parameters of myocardial changes. T1 and T2 mapping are part of the routine CMRT protocol and allow direct quantification of T1 and T2 relaxation times in the myocardium as well as the calculation of extracellular volume. These are important biomarkers both for the diagnosis of various myocardial diseases and for monitoring treatment follow-up and determining prognosis. The purpose of this article is to provide a brief overview of the basic principles of the T1 and T2 mapping techniques, as well as their main applications in different types of cardiomyopathies.